Acute cardiorenal decompensation in the setting of chronic renal artery stenosis treated with successful renal artery stenting. A case report - Ahmed, Nehaal (2025)
Atherosclerotic renal artery stenosis may present with resistant hypertension, hypertensive crisis, ischemic nephropathy, and cardiac destabilization. Although early studies of renal artery stenting showed promise, later trials found no benefit over medical therapy—yet often excluded high-risk, acute cases. We describe an 85-year-old male with cardiovascular risk factors who developed a hypertensive crisis, acute kidney injury, and flash pulmonary edema. An angiogram revealed severe ostial right renal artery stenosis. Stenting resulted in the rapid resolution of the acute crisis and restoration of baseline renal function. This case underscores the potential benefit of revascularization in select high-risk presentations of renal artery stenosis.